Frayer model-based assessment for detecting students’ conceptual understanding in evolution - Prativi, Ramadanti; Ramli, Murni; Rinanto, Yudi (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study aimed to test the validity, reliability, and difficulty level of items developed based on the Frayer model and detect conceptual understanding of high school students in biology evolution. The test method evaluated 35 multiple-choice questions on evolution for 55 high school students. Rasch analysis was performed to assess the validity, reliability, difficulty level of items, and students’ ability level. Two experts empirically tested and analyzed the validity of the items. The assessment developed was discovered to be valid based on expert and empirical analyses. Furthermore, the construct validity test indicated that only two of the 35 questions were deemed invalid. The assessment exhibited reliability with an item reliability score of 0.92. The item difficulty levels were equally spread across the normal curve, encompassing questions ranging from very difficult to very easy categories, as depicted in the variable map. After analyzing the map, it was observed that variations in students’ proficiency levels at answering questions were evident, indicating diverse levels of ability. Students performed well in handling formal and superordinate-subordinate level questions. However, their performance differed when dealing with identity and principle-level concepts.